Sackett - L'Amour, Louis (Bantam)
His dream was to build magnificent steamboats to ply the rivers of the American frontier. But when Jean Talon began his journey westward, he stumbled upon a deadly conspiracy involving a young woman$1 (Bs search to find her missing brother, and a ruthless band of renegades. Led by the brazen Baron Torville, this makeshift army of opportunists is plotting a violent takeover of the Louisiana Territory. Jean swears to find a way to stop this daring plan. If he doesn$1 (Bt, it will not only put an end to all his dreams; it will change the course of history$1 (Band destroy the promise of the American frontier.s
64589
Keywords: Explorers; History; Indian women; Kickapoo Indians; Love stories; Natchez Indians; Pioneers; United States -- History -- Fiction -- Colonial period, ca. 1600-1775